2017
DOI: 10.1021/acssuschemeng.7b02513
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flavonoid-Functionalized Silk Fiber Presenting Antibacterial, Antioxidant, and UV Protection Performance

Abstract: Natural bioactive compounds as promising alternatives to synthetic finishing agents have recently gained increasing attention in the textile industry due to their eco-friendliness, low irritation, and biocompatibility. The present study reports a sustainable approach for preparing antibacterial, antioxidant, and UV-protective silk fiber using two natural flavonoids (quercetin and rutin) by an adsorption technique. The adsorption kinetics and isotherms of the two flavonoids were investigated, and their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…This result indicates that the AgNPs prepared by flavonoids can improve the antioxidant activity of silk. However, the silk samples treated with the flavonoid prepared AgNPs displayed much lower antioxidant activity than those directly treated with the equivalent concentration of flavonoids according to our previous work [21]. This is due to the fact that the phenolic hydroxyl groups of catechol moiety in the B ring of the flavonoids are mainly responsible for radical scavenging [48], but they are oxidized and converted into the quinine form during the AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 90%
“…This result indicates that the AgNPs prepared by flavonoids can improve the antioxidant activity of silk. However, the silk samples treated with the flavonoid prepared AgNPs displayed much lower antioxidant activity than those directly treated with the equivalent concentration of flavonoids according to our previous work [21]. This is due to the fact that the phenolic hydroxyl groups of catechol moiety in the B ring of the flavonoids are mainly responsible for radical scavenging [48], but they are oxidized and converted into the quinine form during the AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 90%
“…In recent years, innovative ‘biofunctional’ applications have been receiving attention in the field of cosmetotextile technology, mostly to meet the needs of people with highly sensitive skin. These kinds of material are indeed becoming diffusely appreciated as an innovative vehicle for the local treatment of skin diseases caused by microbial agents [6,7] or sunlight induced photooxidation [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids and phenolic acids are among the most important chemical classes exhibiting antioxidant activity, mostly via radical-scavenging mechanisms [8,11]. This evidence along with the their strong interactions with fiber material has fueled the interest by scientists towards the functionalization of textiles by these molecules [8,12,13]. In this context, natural dyes, extracted from various species of wild plants or crops, are particularly appreciated because, in addition to the aforementioned beneficial biofunctional properties, they are also able to confer peculiar soft colors with a unique shade.…”
Section: Introductionmentioning
confidence: 99%
“…The basic structural feature of flavonoid compounds is the 2-phenyl-benzo pyrane or flavan nucleus, which consists of two benzene rings linked through a heterocyclic pyrane ring (Figure 4 It has been reported that quercetin, a flavonoid, imparted better antioxidant, antibacterial and UV protection performance to silk fabric [81]. Flavonoids and anthocyanin from red onion skin (Allium cepa L.) are natural dyes with antibacterial activity and UV protection after application on wool and cotton fabric [82].…”
Section: Flavonoidsmentioning
confidence: 99%